Azolla microphylla sebagai Alternatif Sumber Pupuk Organik dalam Budidaya Padi di Lahan Pasir Pantai - Aktavia Herawati; Mujiyo Mujiyo; Slamet Minardi; Ganjar Herdiansyah; Widyatmani Sih Dewi; Nuraini Dwi Agustina Putri (PRIMA: Journal of Community Empowering and Services, 2024)
Azolla microphylla as an Alternative Source of Organic Fertilizer in Rice Cultivation on Sandy Soil Field. Rice (Oryza sativa L.) is a commodity that has high economic value in Srigading Village, Sanden District, Bantul Regency. Azolla is a water fern that has high potential as a source of organic fertilizer. The use of azolla as a source of organic fertilizer is not widely known. The partner involved in this activity is Majelis Taklim Nailul Hidayah, which is not economically/socially productive, but its main livelihood is farming, especially rice. The rice cultivation system carried out by partners so far is still based on the conventional system, which utilizes chemical fertilizers. Azolla can serve as a source of organic fertilizers, acting as a substitute for or reducing the need for chemical fertilizers, thereby reducing dependence on them. The activity aims to increase partners' understanding of utilizing azolla for organic fertilizers through azolla cultivation, which is a straightforward process. The method planned for this activity involves explaining the introduction and development of azolla, as well as practicing the technique of multiplying azolla. The stages of the activity included site surveys, hands-on azolla cultivation, and the application of azolla to rice plants in sandy soil. The results showed that the partners already knew how to cultivate azolla, how to apply azolla, and the benefits of azolla on rice growth. Azolla microphylla was cultivated in ponds lined with tarpaulins measuring 2 m x 3 m x 0.5 m, using 0.5 kg of fresh azolla seedlings. Azolla was harvested 2 weekafter sowing, with one pond producing 37.5 kg of wet azolla, representing a 75-fold increase and a productivity of 12.5 kg/m³.